Density of warm ionized gas near the Galactic center: low radio frequency observations. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Roy, Subhashis
Abstract: We have detected 62 compact likely extragalactic sources in the Galactic center (GC) region at 0.154 and 0.255 GHz with the Giant Metrewave Radio Telescope (GMRT). Their scattering sizes go down linearly with angular distance from the GC up to about 1°. These are more than 10 times lower than the proposed Hyperstrong scattering model within 0.5° from the GC. We also detect 7 out of 10 EG sources expected in the region from existing catalogs. Ionized interfaces of dense molecular clouds to the ambient medium are likely responsible for strong scattering. However, dense GC clouds traced by CS J = (1 − 0) emission are found to have a narrow distribution of ∼0.2° across the Galactic plane. Lack of strong scattering towards EG sources within ∼ 0.5° from GC with | b | ≳ 0.2° could explain our results.